العنف كظرف مشدد لجريمة السرقة فى القانونين السورى والمصرى - حمود، فراس حامد; المخول، عيسى مد الله (جامعة البعث, 2018)
All criminal legislation seeks to assess the punishment in accordance with the criminal danger and the psychological state of the offender in order to preserve the society and establish the system of the society on the one hand, and safeguarding the rights and freedoms of individuals on the other hand. In the field of protection of funds, the legislator addressed the physical assault that the victim may be subjected to by the perpetrators In the crime of theft, promised a circumstance aggravated, so this study dealt with violence as a circumstance aggravating the crime of theft in terms of definition, and to specify the conditions to be available in order to prepare an aggravating circumstance for the crime of theft, while studying the cause of the severity of the penalty for the availability of this circumstance. This research also addressed the equality of punishment between violence and the threat of weapons in regulating the crime of theft, the role of violence in increasing the punishment and changing the legal description of the crime. This research reached a number of results, including not to stipulate a definition of violence in the provisions of the law, the need for violence against human beings, and that violence emphasizes the crime, even if it does not occur to the person of the victim, but rather to someone else. As well as the need for violence to be contemporary to the crime of theft, and that violence had a role in changing the legal description of the crime. The study reached recommendations such as the need to define the general road within the provisions of the law, and to include the definition of roads within cities and villages, and the need to tighten the punishment for thefts that occur during a deputy through violence.
تسعى التشريعات الجزائية كافة إلى تقدير العقوبة بما يتلاءم مع الخطورة الإجرامية والحالة النفسية للجاني بغية حفظ كيان المجتمع وإقرار النظام فيه من جهة، وصون حقوق الأفراد وحرياتهم من جهة أخرى، وفي مجال حماية الأموال تصدى المشرع للاعتداء الجسدي الذي قد يتعرض له المجني عليه من قبل الجناة في جريمة السرقة، وعده ظرفا مشددا، لذا تناول هذا البحث العنف كظرف مشدد لجريمة السرقة من حيث تعريفه، وبيان الشروط الواجب توافرها فيه لكي يعد ظرفا مشددا لجريمة السرقة، مع دراسة العلة من تشديد العقوبة لتوافر هذا الظرف. كما تناول هذا البحث العلة من المساواة في العقوبة بين العنف والتهديد بالسلاح في معرض تنظيم أحكام جريمة السرقة، ودور العنف في تشديد العقوبة وتغيير الوصف القانوني للجريمة. وقد توصل هذا البحث إلى عدد من النتائج منها عدم النص على تعريف للعنف في نصوص القانون، وضرورة وقوع العنف على إنسان، وأن العنف يشدد عقوبة الجريمة ولو لم يقع على شخص المجني عليه، وإنما وقع على شخص آخر غيره. وكذلك ضرورة أن يكون العنف معاصرا لجريمة السرقة، وأن العنف له دور في تغيير الوصف القانوني للجريمة. وقد توصل البحث إلى توصيات منها ضرورة وضع تعريف للطريق العام ضمن نصوص القانون، وأن يشمل التعريف للطرقات داخل المدن والقرى، وضرورة تشديد العقاب على السرقات التي تقع أثناء نائبة بواسطة العنف.
Keywords: القانون المصرى; القانون السورى; العنف; تشديد العقوبة; جريمة السرقة